NLRP3 Overexpression Associated With Poor Prognosis and Presented as an Effective Therapeutic Target in Osteosarcoma - Zhen Huang; Zhen Huang; Zhen Huang; Hui Chen; Shenglin Wang; Hongxiang Wei; Xinwen Wang; Rongkai Shen; Yunqing Wang; Rongjin Lin; Jianhua Lin; Jianhua Lin (Frontiers Media S.A., 2021)
Despite the development of diagnostic and treatment strategies, the survival outcome of patients with osteosarcoma remains poor. Nod-like receptor protein 3 (NLRP3) plays a crucial role in the inflammasome pathway, which is related to the progression of various tumors. However, the effect of NLRP3 on osteosarcoma has not yet been well explored. Our study aimed to investigate the role of NLRP3 in the malignant biological behavior of osteosarcoma as well as its therapeutic value. Immunohistochemistry was applied to investigate the NLRP3 expression in osteosarcoma and osteochondroma specimens. Cell Counting Kit-8, colony formation, wound healing, transwell, and flow cytometry assays were used to explore the contribution of NLRP3 to the proliferation, migration, invasion, apoptosis and cell cycle distribution of osteosarcoma cells in vitro. Western blot was performed to evaluate the expression of NLRP3 and the related proteins in osteosarcoma cell lines after the blockade of NLRP3 using CY-09 and lentivirus intervention. Furthermore, tumor formation assay was used to analyze the effect of NLRP3 on the growth of osteosarcoma in vivo. The results showed that the NLRP3 protein was overexpressed in osteosarcoma, which was independently correlated with the poor prognosis of patients. Moreover, NLRP3 suppression by the inhibitor of CY-09 or lentivirus-induced gene knockdown inhibited the cell proliferation, migration, invasion and promoted the cell apoptosis and G1 cell cycle arrest in osteosarcoma via targeting the inflammasome pathway. Our in vivo results confirmed that the inhibition of NLRP3 suppressed the tumor formation of osteosarcoma. In conclusion, NLRP3 may be regarded as an independent prognostic biomarker and a potential therapeutic target for osteosarcoma.